Finite-time H∞ filtering for discrete-time Markovian jump systems with partly unknown transition probabilities - Cheng, Jun; Zhu, Hong; Zhong, Shouming; Zhang, Yuping; Li, Guihua (Canadian journal of physics, 2013)
This paper addresses the problems of finite-time stochastic stability and stabilization for linear Markovian jump systems subject to partial information on the transition probabilities. By introducing bounded finite time and stochastic character, sufficient conditions that can ensure bounded finite time and H ∞ finite-time bounded filtering are derived. Finally, an example is given to illustrate the efficiency of the proposed method.